Soziale Bewegungen und Gewerkschaften im Wechselspiel - Pernicka, Susanne (Forschungsjournal Soziale Bewegungen, 2019)
Vereinzelte Verweise auf westmitteleuropäische Länder, die USA oder Australien machen aber deutlich, dass die neoliberale Politik auch in diesen Ländern zu einer Verschärfung der Spaltungen zwischen verschiedenen Gruppen auf dem Arbeitsmarkt und zwischen diesen und den "Abgehängten" ohne Aussicht auf eine dauerhafte Integration in den Arbeitsmarkt geführt hat. Die Fragen nach der Nachhaltigkeit von Allianzen zwischen Gewerkschaften und sozialen Bewegungen, den politischen und gesellschaftlichen Orientierungen (kosmopolitische Öffnung versus nationalistische und gruppenspezifische Schließungen) sowie deren Effekten bleiben aber letztlich offen und können durch den Verweis auf Polanyis "Pendel" zwischen ökonomischer Liberalisierung und protektionistischer Gegenbewegung kaum zufriedenstellend beantwortet werden. Wie die Herausgeber des Sammelbandes in den Schlussfolgerungen betonen, handelt es sich bei der aktuellen Phase des Neoliberalismus um eine seit mehreren Dekaden andauernde Bewegung von oben, die ungeachtet der Finanz- und Eurokrise(n) ihre hegemoniale Stellung kaum eingebüßt und bestehende Spaltungen und Konflikte zwischen und innerhalb von Gewerkschaften, sozialen Bewegungen und Parteien stark vergrößert hat.
Keywords: Polanyi's pendulum; pendulum; social movements

Ideen und Interessen. Zum Verhältnis von Religion und wirtschaftlicher Entwicklung - Deutschmann, Christoph (Ideas and interests. On religion and economic development, 2013)
While concentrating on the rise of modern capitalism, Weber’s seminal studies have little to say about the impact of religions on contemporary economic development. The paper comments about recent approaches to find an answer to the questions Weber left open. If one disregards a priori constructions of culturalist and rational-choice-theories, these approaches end up again in restating the circular relationship between ideas and interests showed already by Weber, albeit clearly with a higher emphasis on interests. However, the author argues that it would be premature to interpret this result simply as a confirmation of Weber’s “disenchantment” thesis. Rather, it goes back to the transformation of the economy itself into an entity that preaches “values”, proclaims “visions” and in this sense develops an affinity to religious movements. The author deepens this view by referring to Marx’ and Polanyi’s interpretation of capitalism as a system of disembedded markets. The disembedding of markets gives rise to a historically new potential of social uncertainty which the actors need to cope with, thereby developing symbolisms showing striking affinities with religious forms. Nevertheless, the analogies between capitalism and religion are limited. (English)
Keywords: Entgrenzung; Institutionen; Kontingenz; Märkte; Säkularisierung; WEBER, Max, 1864-1920; Werte; capitalism; capitalism - religious aspects; consumption (economics); contingency; disembedding; economic aspects; economic development; institutions; markets; philosophy; religion; religion and sociology; religious aspects; secularization; values

Wealth and Poverty in Postindustrial Societies. The Pragmatistic Approach to Their Empirical Assessment - Kreutz, Henrik (Angewandte Sozialforschung, 2007)
On the terms of Karl Polányi's concept of the "Commodity Fiction" a theoretical conception of poverty is developed, which defines "absolute poverty" as a process, the terminal state of which is "annihilation". Within this process of "totalitarian consumption" consumer goods do not serve human needs in the first line but turn more and more into "consuming goods" which destroy the independence of human actors step by step and finally transform them into "cyborgs", i.e. creatures, whose lives and intentions become fictions of this system of totalitarian consumption.
Keywords: absolute poverty; commodity fiction; consumer goods; consumerism; consumption (economics); fictitious commodities; income distribution; postindustrial societies; poverty; wealth

Karl Polanyi: The Great Transformation - Ebner, Alexander (Schlüsselwerke der Wirtschaftssoziologie, 2021)
Karl Polanyi war in jungen Jahren Zeitzeuge der vielschichtigen ökonomischen, sozialen und politischen Umwälzungen in der österreichisch-ungarischen Donaumonarchie. 1886 in Wien geboren, wuchs er in Budapest auf, wo er Rechtswissenschaft und Philosophie studierte, um dann nach der Zerschlagung der ungarischen Räterepublik nach Wien zurückzukehren. Dort schrieb er für die wirtschaftspolitische Wochenzeitschrift „Österreichischer Volkswirt“.
Keywords: biography

Karl Polanyi - The Life and Works of an Epochal Thinker - Thurnher, Armin; Aulenbacher, Brigitte; Novy, Andreas; Marterbauer, Markus; Polanyi Levitt, Kari (2020)
On 8 May 2018, the International Karl Polanyi Society was founded in Vienna. This marked the beginning of a new phase of engagement with a thinker who had already come to be regarded as a centennial figure in the Anglo-Saxon world. This book serves as an introduction to The Great Transformation, Polanyi’s magnum opus and one of the most important works of the 20th century. It helps us to understand the background to Karl Polanyi’s intellectual career, sketches the lives of his family members, describes the milieus of Budapest, Vienna, London and New York, which were such informative influences in his life, and sheds light on his relationship with contemporaries such as Keynes, Mises and Hayek. Renowned Polanyi researchers, including, most notably his daughter Kari Polanyi Levitt, elucidate Polanyian concepts such as ‘fictitious commodities’ and apply his analysis to an era when everything seems to be subjected to the mechanics of the market.
Keywords: Great Transformation, The (Book); fictitious commodities